Investigation of Biodiversity Awareness and Conservation Behaviors on Science Teachers Candidates - Ozyurt, Zeynep; Turkoglu, Ismail; Bahoeci, Ferhat (Acadlore Publishing House, 2025)
This study investigates the levels of biodiversity awareness and conservation behaviours among science teacher candidates and examines the extent to which these levels vary across demographic and academic variables. A survey-based research design was employed, involving 216 teachers candidates enrolled in the Science Education program within the Department of Mathematics and Science Education at the Faculty of Education. Data were collected using the Biodiversity Awareness Measurement Tool (BAMT) and the Biodiversity Behaviour Measurement Tool (BBMT). Analysis revealed that the mean biodiversity awareness score was 3.57 +/- 0.328, whereas the mean conservation behaviour score was 3.53 +/- 0.370. A statistically significant gender-based difference was observed in biodiversity awareness, with female participants exhibiting higher awareness levels; however, no significant difference was detected in conservation behaviours. Class level was found to exert a partial influence on both awareness and behaviour scores. Notably, 93.5% of participants reported never having engaged in biodiversity-related activities, indicating a substantial gap between awareness and active conservation efforts. This disconnect underscores a critical challenge in translating theoretical knowledge into practical engagement in biodiversity preservation. Biodiversity is fundamental to ecosystem stability, species sustainability, and human well-being, yet it remains under threat due to rapid urbanisation, industrial pollution, agricultural chemical use, and deforestation. Given the role of educators in fostering environmental consciousness, it is imperative that teacher candidates receive comprehensive training in biodiversity conservation and sustainable ecosystem management. While theoretical knowledge is essential, active participation in conservation initiatives is equally crucial. Greater emphasis should be placed on experiential learning approaches that immerse students in ecosystems, foster direct engagement with nature, and cultivate a sense of responsibility for biodiversity protection. It is recommended that environmental education curricula incorporate nature-based activities, ecological restoration projects, and biodiversity monitoring programs. Furthermore, teacher candidates should be encouraged to participate in sustainability initiatives, field-based environmental studies, and community-led conservation efforts. By fostering a deeper connection with nature and embedding biodiversity conservation into educational practice, future generations of educators can be equipped to promote environmental stewardship and instil sustainable values in their students, thereby contributing to the long-term preservation of global biodiversity.
Keywords: Biodiversity awareness; Conservation behaviours; Environmental education; Sustainable ecosystem management; Science teacher candidates